1919
DOI: 10.1086/279691
|View full text |Cite
|
Sign up to set email alerts
|

The Inheritance of Hull-Lessness in Oat Hybrids

Abstract: THE purpose of this paper is to set forth some results obtained in certain crosses between the hull-less types of oats and some of the hulled forms. The hull-less types belong to the species Avena nuda. The origin of these forms is not definitely known, although, according to Carleton,2 they appear to have come from central and eastern Asia. Reports are to the effect that a certain form of this oat has been cultivated in China for a thousand years or longer. These types are not generally cultivated in any othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

1927
1927
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
4
14
0
Order By: Relevance
“…The actions of the different alleles were established considering the involvement of modifying genes. Our results are consistent with the available literature, in which a large number of studies have indicated that the action of one major gene controls multiflorous spikelet formation (Caporn, 1918;Love and McRostie, 1919;Boland and Lawes, 1973;Kibite and Taylor, 1994;Cabral et al, 2000). Phenotypic screening for the multiflorous spikelet trait clearly demonstrated a 1:1 ratio, in which approximately 50% of the evaluated RILs for both genetic populations exhibited 100% normal spikelets.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The actions of the different alleles were established considering the involvement of modifying genes. Our results are consistent with the available literature, in which a large number of studies have indicated that the action of one major gene controls multiflorous spikelet formation (Caporn, 1918;Love and McRostie, 1919;Boland and Lawes, 1973;Kibite and Taylor, 1994;Cabral et al, 2000). Phenotypic screening for the multiflorous spikelet trait clearly demonstrated a 1:1 ratio, in which approximately 50% of the evaluated RILs for both genetic populations exhibited 100% normal spikelets.…”
Section: Discussionsupporting
confidence: 91%
“…The inheritance of the multiflorous spikelet trait has been investigated in several studies over the past century, and the results have indicated that the action of a major gene controls the trait and has a strong effect on the phenotype (Caporn, 1918;Love and McRostie, 1919;Boland and Lawes, 1973;Kibite and Taylor, 1994;Cabral et al, 2000). However, oat breeders and researchers believed that this major gene also participated in the formation of naked grains (Simons et al, 1978;Ougham et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated the character controlled by a single gene with a strong effect on the phenotype (Gaines 1917, Caporn 1918, Love and McRosstie 1919, Boland and Lawes 1973, Cabral et al 2000. Therefore, the results of the genetic analysis for the UFRGS 01B71114-1-3 x UFRGS 006013-1 population corroborate the results reported in previous studies.…”
Section: Resultssupporting
confidence: 85%
“…This fact may be associated with the number of panicles evaluated and/or erroneous classification of the panicles in the F 2 generation. The same occurred in studies carried out by Gaines (1917) and Love and McRostie (1919), which also showed non-standard behavior in the F 3 generation, thus affirming that the panicles of the F 2 generation had been wrongly classified, i.e., that hulled grains could have been dehulled during threshing, or that other factors affected the expression of naked grains. In spite of the small number of panicles evaluated in this study, the data of the F 3 generation show agreement (Table 4) with the hypothesis proposed in the F 2 generation (Table 3).…”
Section: Resultssupporting
confidence: 67%